Supporting peace after civil war: what kind of international engagement can make a difference? - Charlotte Fiedler; Jörn Grävingholt; Karina Mross (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
How can international actors effectively support peace after civil war? So far, empirical research has established that peacekeeping can be an effective instrument in maintaining peace, but little systematic knowledge exists on the roles that other types of peace support can play. International peacebuilding encompasses a broad range of activities beyond peacekeeping. It includes non-military support to increase security through disarmament, demobilisation, the reintegration (DDR) of former combatants, as well as security sector reform (SSR) and demining; support for governance to strengthen political institutions and state capacity; support for socioeconomic development to create a peace dividend through reconstruction, basic services, jobs and macroeconomic stability; and support for societal conflict transformation, including reconciliation, dialogue and transitional justice programmes. This briefing paper presents the results of a comprehensive analysis of disaggregated external support in post-conflict situations, undertaken recently within the DIE research project “Supporting Sustainable Peace”. Analysing combinations of peace support provided during the first five years of 36 post-civil war episodes since 1990, we find that international peacebuilding can clearly make a difference. More specifically, our findings show that international peacekeeping is one, but not the only, means of support associated with sustained peace; contrary to concerns regarding the destabilising effects of democratisation, the majority of successful cases are in fact characterised by substantial international support in the field of politics and governance in democratising contexts; only combined international efforts across all types of support can help prevent renewed conflict in contexts of a high risk of recurrence; and countries that did not receive any substantial peace support experienced conflict recurrence within five years. In light of these findings, we recommend the following to the international community when faced with post-civil war situations: Engage substantially in post-conflict countries. Our results show that international peacebuilding can be effective, even where there is a high structural risk of conflict recurrence. While success will never be guaranteed, countries that receive substantial international support often remain peaceful, whereas all countries that were neglected by the international community experienced conflict recurrence. Pay particular attention, and provide substantial support, to the field of politics and governance in post-conflict countries that begin to democratise. While it is well known that democratisation processes are conflict prone, our analyses demonstrate that donor engagement geared towards supporting such processes can help mitigate conflict and contribute to peace. When a post-conflict country has decided to embark on political reforms donors should offer governance support to help overcome potential destabilising effects of democratisation processes. Invest in an international approach that encompasses all areas of peacebuilding early on after the end of a civil war. Especially in contexts with a high structural risk of renewed violent conflict, the chances of sustained peace are increased by simultaneous support for security, institutions, livelihoods and societal conflict transformation.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Sicherheit; Frieden und fragile Staaten